Interactive Mesh Smoothing for Medical Applications. (30th July 2013) - Mönch, Tobias; Lawonn, Kai; Kubisch, Christoph; Westermann, Rüdiger; Preim, Bernhard
<x xml:space="preserve">Abstract</x> Surface models derived from medical image data often exhibit artifacts, such as noise and staircases, which can be reduced by applying mesh smoothing filters. Usually, an iterative adaption of smoothing parameters to the specific data and continuous re‐evaluation of accuracy and curvature is required. Depending on the number of vertices and the filter algorithm, computation time may vary strongly and interfere with an interactive mesh generation procedure. In this paper, we present an approach to improve the handling of mesh smoothing filters. Based on a GPU mesh smoothing implementation of uniform and anisotropic filters, model quality is evaluated in real‐time and provided to the user to support the mental optimization of input parameters. This is achieved by means of quality graphs and quality bars. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>